2004
DOI: 10.1080/13102818.2004.10817117
|View full text |Cite
|
Sign up to set email alerts
|

Anther Culture of Pepper (Capsicum AnnuumL.): Comparative Study on Effect of the Genotype

Abstract: There were investigated and compared the in vitro response in anther culture of 16 Bulgarian pepper (Capsicum annuum L.) genotypes: six lines, six varieties and four hybrids developed in Maritsa Vegetable Crops Research Institute, Plovdiv. The anthers reacted with induction of direct embryogenesis or callusogenesis. Only in two of the studied genotypes (line N145 and variety Zlaten medal) the anthers have shown indirect organogenesis. There were established genotypes with good embryogenic ability-varieties Zla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…These results, i.e. genotype dependence on androgenic response are in consistent with the reports of several earlier workers (Dumas de Vaulx et al, 1981;Rodeva et al, 2004;Lantos et al, 2009;Zhao et al, 2010;Niklas et al, 2012;Liljana et al, 2013;Luitel andKang, 2013 andOlszewska et al, 2014).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…These results, i.e. genotype dependence on androgenic response are in consistent with the reports of several earlier workers (Dumas de Vaulx et al, 1981;Rodeva et al, 2004;Lantos et al, 2009;Zhao et al, 2010;Niklas et al, 2012;Liljana et al, 2013;Luitel andKang, 2013 andOlszewska et al, 2014).…”
Section: Resultssupporting
confidence: 82%
“…The genotype is the most important and often limiting factor in the pepper androgenic response (Wang and Zhang, 2001;Rodeva et al, 2004;Liu et al, 2007;Lantos et al, 2012). The results of the present in vitro anther culture study on capsicum hybrids Bharat and Indra amply demonstrated genotypic differences in response of anther culture.…”
Section: Resultsmentioning
confidence: 56%
“…These results agree with those obtained by Nowaczyk et al (2009) who examined the reaction of F 2 C. annuum genotypes and observed the effect of genotypes in the response to embryo induction, and variations ranged from 0 to 39 embryos in 100 anthers. Similar results were previously described by Rodeva et al (2004) and Nowaczyk and Kisiala (2006).…”
Section: Induction Of Embryogenic Calli and Embryossupporting
confidence: 81%
“…The genotype effect was also observed by Rodeva et al (2004) in a study examining the response of different C. annuum genotypes and F 1 hybrids that were cultured according to the protocol of Dumas de Valux et al (1981). The results indicated wide variation in callus formation between genotypes that showed no callus formation (F 1 : 1647 x 1962) to those that induced up to 16.6% of calli (Genotype 146).…”
Section: Induction Of Embryogenic Calli and Embryosmentioning
confidence: 94%
“…Genotype limitations of the mean androgenic capacity for haploid embryo production have been found in Solaneceae, such as tomato , potato (Irikura, 1975), pepper (Abak, 1984;Rodeva et al, 2004;Irikova et al, 2011), and eggplant (Tuberosa et al, 1987;Salas et al, 2011).…”
Section: Resultsmentioning
confidence: 99%